Integration Of Real Time Pile Design By Means Of Building Information Modeling - Johannes Beck; Prof. Dr. -Ing. habil. Sascha Henke (Deep Foundations Institute, 2022)
The growth of Building Information Modeling (BIM) during recent years opens possibilities for integrating new digitally driven design approaches. While parametric design and algorithmic design slowly gains popularity in numerous ACE-applications, e.g. bridge design, it is rarely used by geotechnical professionals. This article presents an approach for implementation of parametric design in the BIM-based geotechnical design process. The methodology is applied to pile design and enables a real time design analysis according to DIN EN 1997-1 and EA-Pfähle 2012 considering boundary conditions such as pile position and layout, pile geometry, soil stratification and soil properties. By using intelligent attributes and scripts to control, calculate and assign them, the design analysis is directly executed in the BIM-software environment, in this case Autodesk Revit with Dynamo. This BIM integrated design approach allows multi-criteria evaluations of pile designs using aspects such as costs, environmental impact or constructability in addition to the commonly examined structural analysis criteria. As the proposed models are fully parametric, generative optimization algorithms can be applied to identify the ideal design for the entirety and each of the piles. Finally, the potential and limits of this methodology with respect to modeling, analysis, simulation and optimization are discussed.